Penguatan Peran Kelompok Swadaya Masyarakat dalam Pengelolaan Sampah Domestik di Kawasan Permukiman: Pengabdian - Aria Dian Tri Wahyuni; Arinda Eka Lidiastuti; Khalilah Daud Isaac Makhmut; Hani Widhianata; Ika Wardani; Arini Zulfaida (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The issue of domestic waste management in Indonesia remains a significant challenge, especially at the household level in residential areas. Despite existing regulations and community-based waste management efforts, implementation in the field still faces various obstacles such as a lack of awareness and institutional support. This study conducted a community service intervention by strengthening the role of the Community Self-Help Group (Kelompok Swadaya Masyarakat, KSM) in RW 01, Rampal Claket Village, Malang City, through training, technical facilitation, and the development of a community-based waste management model using a Participatory Action Research (PAR) approach. The results show a significant increase in residents’ participation in sorting, managing, and recycling waste, as well as the strengthening of KSM’s organizational capacity in operational management and waste-based entrepreneurship. This program contributed to the reduction of inorganic waste volume sent to the Final Disposal Site (Tempat Pembuangan Akhir, TPA), empowered the community’s micro-economy, and enhanced environmental awareness. These findings emphasize the importance of triple helix collaboration among universities, government, and communities in building an effective, sustainable waste management system with positive socio-ecological impacts.